Development of Problem-Based E-Student Worksheets Integrated with Ethno-STEM on Global Warming Material to Enhance Chemical Literacy - Jajang Jalaluddin; Sri Haryani; Nuni Widiarti (Jurnal Inovasi Pendidikan Kimia, 2025)
This study aimed to develop a Problem-Based Learning (PBL) electronic Student Worksheet (e-LKPD) integrated with Ethno-STEM, focusing on global warming in the context of mangrove forests and water hyacinth plants, to enhance students’ chemical literacy. The research subjects consisted of 36 students from class X A (experimental group) and 36 students from class X J (control group) at MAN 2 Semarang. The study employed a Research and Development (R&D) design following the 4D procedural model by Thiagarajan (1974), modified into three stages: Define, Design, and Development, as the Dissemination stage was not conducted. Data were collected through questionnaires, interviews, validation by content and media experts, and chemistry literacy tests. Quantitative analysis was performed using pretest-posttest comparisons and normalized gain (N-gain) calculations. The results indicate that the e-LKPD achieved high validity in both material and media aspects. Small-scale trials showed that the e-LKPD was highly engaging for students, while the N-gain test in the experimental class reached 0.8492, categorized as high. These findings suggest that the Ethno-STEM-integrated PBL e-LKPD is highly suitable as instructional material. It effectively improves chemical literacy by integrating knowledge, context, competence, and attitude, while also providing an interactive and culturally contextualized learning experience. This study demonstrates the potential of culturally integrated STEM-based teaching materials to enhance conceptual understanding, critical thinking, and student engagement in chemistry education.